2013
DOI: 10.2350/11-01-0968-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Sarcoma of Kidney: Morphoproteomic Analysis Reveals Genomic Correlates and Therapeutic Options

Abstract: Results: The results of immunohistochemistry and EBER are shown in the table. Survivin and Bax were expressed strongly in all the cases, and the pattern of staining was both nuclear and cytoplasmic. No apparent correlation was seen between the expression of EBER and p5. CC p5 Bax Survivin Bcl-2 EBER Absent 56% 6% 0% 0% 6% 64% Weak 42% 92% 0% 0% 5%-Strong 2% 2% 100% 100% 2% 6% Conclusions: Our study demonstrates abnormalities in the apoptotic pathways in HRS cells in pediatric cHL. Down-regulation of p53 may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Because none of our CCSK had the YWHAE-FAM22 translocation, cyclin D1 overexpression in CCSK likely results from a different mechanism, possibly involving upregulation of the Sonic Hedgehog pathway. In a study of 3 cases of CCSK, what the authors term a “morphoproteomic analysis” (essentially a immunohistochemical survey) of the sonic hedgehog, nuclear factor kappa B (NF-κB), and mammalian target of rapamycin pathways showed involvement of these pathways, explaining cyclin D1 overexpression on this basis [5]. Gene expression profiling studies of CCSK have demonstrated upregulation of neural markers and activation of the Sonic Hedgehog and PI3K/Akt pathways with upregulation of PTCH, GLI1, GLI2, TWIST1, PDGFRA, PDGFA , and CCND1 [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because none of our CCSK had the YWHAE-FAM22 translocation, cyclin D1 overexpression in CCSK likely results from a different mechanism, possibly involving upregulation of the Sonic Hedgehog pathway. In a study of 3 cases of CCSK, what the authors term a “morphoproteomic analysis” (essentially a immunohistochemical survey) of the sonic hedgehog, nuclear factor kappa B (NF-κB), and mammalian target of rapamycin pathways showed involvement of these pathways, explaining cyclin D1 overexpression on this basis [5]. Gene expression profiling studies of CCSK have demonstrated upregulation of neural markers and activation of the Sonic Hedgehog and PI3K/Akt pathways with upregulation of PTCH, GLI1, GLI2, TWIST1, PDGFRA, PDGFA , and CCND1 [6].…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell sarcoma of the kidney lacks a distinctive immunophenotype, and the cell of origin of CCSK is not clear. Recent reports suggest that nerve growth factor receptor (NGFR) and cyclin D1 immunoreactivity may be used to support a diagnosis of CCSK [5,6]. However, NGFR is not an immunohistochemical stain that is widely available in most pathology departments at present.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular tests for detecting BCOR gene abnormalities are not available especially in developing countries such as ours. Recently, a number of studies have suggested that immunohistochemical stain Cyclin D1 is useful in distinguishing CCSK from some pediatric renal neoplasms [3, 5, 19]. More importantly, recent studies suggest that BCOR immunohistochemistry appear to be highly sensitive and specific for the diagnosis of CCSK based on the recently identified BCOR gene abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the previous decades, genetic studies regarding CCSK have been limited and the underlying mechanism of the disease consequently remains unclear. Dhamne et al ( 5 ) reported that cyclin D1 (CCND1) may be a central molecule in the pathogenesis of CCSK, primarily regulated by nuclear factor κB (NF-κB) cells. Forkhead box D1 and cbp/p300-interacting transactivator, with Glu/Asp-rich carboxy-terminal domain 1, are highly expressed in CCSK, with oxidative-stress-responsive kinase 1, an early embryonic marker, also expressed at high levels in CCSK and at greater levels than observed in normal kidneys or Wilms' tumors (WT) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%